The changing landscape of cerebral revascularization surgery: A United Kingdom experience - Gallagher, Mathew J.; Frantzias, Joseph; Kailaya-Vasan, Ahilan; Booth, Thomas C.; Tolias, Christos M. (Frontiers in Radiology, 2022)
Objective We describe the chronological trends in cerebral revascularisation surgery through a single surgeons experience; and we review whether in the context of giant and fusiform cerebral aneurysms, flow diverting stents have impacted on the use of cerebral revascularisation surgery. Methods We review our single institution prospectively collected database of cerebral revascularisation procedures between 2006 and 2018. Comparing this to our database of flow diverting endovascular stent procedures we compare the treatment of fusiform and giant aneurysms. We describe patient demographics, procedural incidence, complications and outcomes. Results Between 2006 and 2018, 50 cerebral revascularisation procedures were performed. The incidence of cerebral revascularisation surgery is declining. In the context of giant/fusiform aneurysm treatment the decline in cerebral revascularisation is accompanied by a rise in the use of flow diverting endovascular stents. 30 cerebral revascularisation were performed for moyamoya disease and 11 for giant/fusiform aneurysm. 4 (14%) direct bypass grafts occluded without neurological sequela. Other morbidity included hydrocephalus (2%), transient ischaemic attacks (2%) and ischaemic stroke (2%). There was one procedure related mortality (2%). Flow diverting stents were inserted for 7 fusiform and 7 giant aneurysms. Comparing treatment of giant/fusiform aneurysms there was no significant difference in morbidity and mortality between cerebral revascularisation and flow diverting endovascular stents. Conclusions We conclude that with the decline in incidence of cerebral revascularisation surgery there is a need for centralisation of services to allow high standards and outcomes to be maintained.